Implementación de un prototipo de una planta de tratamiento de aguas residuales conectada a IoT para reúso del agua en la finca Villa Viviana (2022)
In the present work, what is related to the implementation of a wastewater treatment plant connected to IoT for reuse in the Villa Viviana farm is documented in order to improve the state of the water resource for washing facades, floors and others. With the implementation of this project, it is possible to reduce the waste of drinking water that is of little access to the farm, defining the requirements of the farm for water treatment, a hydraulic system is implemented with a series of tanks, which have systems for water treatment such as flocculation, sedimentation, disinfection, filter and storage. Additionally, the project has a monitoring through the internet of things (IoT) of the filling level in the flocculation and final storage tanks, the turbidity of the water at the beginning of the system and at the end to evaluate the performance of the plant and achieve a control of the turbidity variable by means of a chemical dosage system based on its measurement, and measurement of the pH of the treated water. The prototype has a manual maintenance system called backwashing, which, by closing valves, guarantees the durability of the filter materials. The prototype has a total capacity of 4,61 m³ distributed in each of its processes (Storage, flocculation and sedimentation, disinfection and filter. The implementation of this prototype gives as a product an improvement in terms of turbidity in the water, decreasing the value of the same up to 20 times with input values of 650 NTU, and output values of 30 NTU. The implementation of this project results in several advantages in the consumption of water in the Villa Viviana farm, since it will be possible to use the water that is available for disposal, in other tasks such as infrastructure cleaning.